Mapping the entire human corneal nerve architecture - He, Jiucheng (2010)
We developed an approach to generate a three-dimensional map that facilitates the assessment of epithelial nerve density in different corneal areas to define aging and gender influence on human corneal nerve architecture. Twenty-eight fresh human eyes from 14 donors of different ages were studied. Corneal nerves were stained and consecutive images acquired with a fluorescence microscope, recorded at the same plane, and merged for viewing the complete epithelial and stromal nerve architecture. After whole mount examination, the same cornea was also used for transection. Stromal nerves entered the cornea in a radial pattern, subsequently dividing into smaller branches. Some branches connected at the center of the stroma, but most penetrated upward into the epithelium. No differences were observed between nerve densities in the four corneal quadrants. Epithelial innervation in the limbal and most of the peripheral area was supplied by a superficial network surrounding the limbal area. Central epithelial nerves were supplied by branches of the stromal nerve network. Epithelial nerve density and terminal numbers were higher in the center of the cornea, rather than the periphery. There were no differences in epithelial nerve density between genders, but there was a progressive nerve density reduction concomitant with aging, mainly in eye samples of donors 70-years of age and older. The modified technique of tissue preparation used for this study allowed for observation of new nerve structure features and, for the first time, provided a complete view of the human corneal nerve architecture. Our study reveals that aging decreases the number of central epithelial nerve terminals, and increases the presence of irregular anomalies beneath the basal layer.